(untitled) (Heritage, 2023)
The aim of the work was to examine the quality of life in the domain of physical, emotional, social and school functioning of students with developmental disabilities who attend inclusive classes. The sample consisted of 80 respondents attending regular schools in the territory of the Republic of Serbia.The structure of the sample consisted of students with developmental disabilities (N-40) and students with regular development (N-40) of both sexes, aged 11 to 16 years.It was used for research purposes The PedsQLTM 4.0 Generic Core Scale. The obtained results showed that the quality of life of all students included in the sample is at an average level. The results confirmed the positive effects of inclusive education, especially in the domain of social functioning of students with disabilities. However, the results indicate that the school environment and the concept of education require permanent improvement in order to raise the quality of life of all students to a higher level.